2005
DOI: 10.1186/1472-6963-5-16
|View full text |Cite
|
Sign up to set email alerts
|

What is important in evaluating health care quality? An international comparison of user views

Abstract: Background: Quality of care from the perspective of users is increasingly used in evaluating health care performance. Going beyond satisfaction studies, quality of care from the users' perspective is conceptualised in two dimensions: the importance users attach to aspects of care and their actual experience with these aspects. It is well established that health care systems differ in performance. The question in this article is whether there are also differences in what people in different health care systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 15 publications
2
35
0
4
Order By: Relevance
“…Not being able to resolve the patient's problem decreases the chance of satisfaction by 61%. This result corroborates those from Bernhart et al 35 and Groenewegen et al 36 who found that the main aspect for service satisfaction was that the user felt that their problem had been resolved.…”
Section: Male Female Totalsupporting
confidence: 83%
“…Not being able to resolve the patient's problem decreases the chance of satisfaction by 61%. This result corroborates those from Bernhart et al 35 and Groenewegen et al 36 who found that the main aspect for service satisfaction was that the user felt that their problem had been resolved.…”
Section: Male Female Totalsupporting
confidence: 83%
“…It is also supported by a recent report that there is about 65 to 75% potential for productivity increase by health workers in Tanzania if working time is spent on productive activities and the activities are done efficiently (Maestad, 2006). Moreover, availability of health professionals has a bearing on the quality of service that is offered and certainly on users' perception as reported from other studies (Smith & Sanderson, 1992;Haddad et al, 1998;Lomoro et al, 2002;Leon, 2003;Groenewegen et al, 2005;Lim et al, 2004;Manongi et al, 2006;Kamuzora & Gilson, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…2 It is thus difficult to know whether variations in patient experiences reflect differences in culture, health systems or actual differences in quality as perceived by patients. 31 Methodological concerns aside, existing research has implied that there is cross-national variation in patient experiences. 32 The Commonwealth Fund and the WHO have conducted surveys of the general population 32 33 and within primary care.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%